DO INNOVATION INCENTIVES WORK? EVIDENCE FROM THE ITALIAN MANUFACTURING SECTOR - Federico Biagi; Massimo Loi (European Regional Science Association (ERSA), 2011)
The main purpose of this study is to investigate upon the impact of fiscal incentives on firm's innovative performance. We use data from the 7th, 8th and 9th waves of the "Indagine sulle Imprese Manifatturiere Italiane" by Unicredit (previously managed by Capitalia-Mediocredito Centrale), which contains information on both product and process innovation by manufacturing firms, on the amount of resources invested in R&D (if such amount is positive) and it is also informative of the existence of forms of fiscal incentive for R&D and investment in innovative activities. In our study we use different techniques. First we look at Average Treatment Effects, under the assumption of "selection on observables", implying that the econometrician has access to all the variables affecting the likelihood of being treated. In this part of the paper we verify whether -everything else constant (i.e. for a given value of the propensity score)- there is evidence that firms that have access to fiscal incentives tend to innovate more. In the second part of our study we cast some doubts on the plausibility of the "selection on observables" assumption and we look more in depth at one specific case of fiscal incentive: the one provided by Law 140/1999 to firms located in "depressed areas" (as defined by the law itself). We focus on this law because it is particularly important from a policy perspective within the Italian dual economy, but also because it allows us a more precise estimate of the treatment effect in a situation where treatment status (i.e. access to the incentive) is likely to depend to the same (unobserved) factors that affect the innovation outcome. In such a situation OLS estimated are biased and inconsistent and we have to use instrumental variable estimation. We choose to instrument treatment using the eligibility rules for treatment and we find the confirmation that indeed an endogeneity issue exists and that its effects are stronger the weaker is the impact of treatment on the outcome variable.
Keywords: 330